Communication with patients who are dispensed a first prescription of chronic medication in the community pharmacy. - van Hulten R; Blom L; Mattheusens J; Wolters M; Bouvy M (Patient Education & Counseling, 2011)
OBJECTIVE: To analyze information and communication in the community pharmacy when patients collect a first dispensing for chronic medication. METHODS: In 3 pharmacies in the South-West of the Netherlands, counter-based communication with patients receiving a first dispensing for chronic medication was observed and audiotaped. Each contact was analyzed by two observers using an observation checklist. An 11-item questionnaire was given to the patients. RESULTS: 72 Patients were included. Only pharmacy technicians provided information. Average contact lasted approximately 2min. A computer checklist to support information giving was closely followed. Interactions were structured with introduction and closure. Mostly, information was given without exploring needs of the patient. Questioning showed open-ended questions (26%); check-questions and questions asking feedback (57%). A mean general score given was 5.8 (range 1-9). Of 46 responders who filled in a questionnaire, the majority felt that information was useful, clear and understandable. CONCLUSION: Our results show a concise and efficient way of information giving, closely related to a computer checklist. Technicians dominate the interaction. They ask few questions. Patients are satisfied about provided information and the contact. PRACTICE IMPLICATIONS: We suggest a more patient-centered way of communication to increase patients' participation and to meet patients' needs for information.